2014
DOI: 10.1080/16506073.2014.980753
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Posttraumatic Stress Symptoms: A Meta-Analysis

Abstract: Emotion regulation (ER) has been identified as a critical factor in the development and maintenance of posttraumatic stress symptoms (PTS; Bardeen, Kumpula, & Orcutt, 2013 [Journal of Anxiety Disorders, 27, 188-196]; Marx & Sloan, 2005 [Behaviour Research and Therapy, 43, 569-583]; Nightingale & Williams, 2000 [British Journal of Clinical Psychology, 39, 243-254]). The current meta-analysis aimed to provide a thorough, quantitative examination of the associations between PTS and several aspects of ER. A search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
218
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(265 citation statements)
references
References 93 publications
29
218
1
7
Order By: Relevance
“…These results concur with the outcome of a recent meta-analysis on the relationships of several aspects of emotion regulation with posttraumatic stress symptoms showing a large association with rumination (r ¼ .51) and a medium association with worry (r ¼ .28) (Seligowski, Lee, Bardeen, & Orcutt, 2015). This difference in predictive power of rumination and worry for onset of PTSD could partly be explained by differences in the temporal orientation of rumination and worry.…”
Section: Discussionsupporting
confidence: 90%
“…These results concur with the outcome of a recent meta-analysis on the relationships of several aspects of emotion regulation with posttraumatic stress symptoms showing a large association with rumination (r ¼ .51) and a medium association with worry (r ¼ .28) (Seligowski, Lee, Bardeen, & Orcutt, 2015). This difference in predictive power of rumination and worry for onset of PTSD could partly be explained by differences in the temporal orientation of rumination and worry.…”
Section: Discussionsupporting
confidence: 90%
“…Results support a congruent relationship between the use of functional and dysfunctional strategies in episodes of anger and sadness and indicators of hedonic and psychological well-being (Seligowski et al, 2015). Forms of affect regulation were also related to well-being (Koval et al, 2014; Visted et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…A recent meta-analysis of emotion regulation and PTSD reported that the largest average effect sizes (for specific strategies, rather than a general inability to regulate emotion) were Personality and Individual Differences 92 (2016) 104-108 for rumination (r = .51), thought suppression (r = .47), and experiential avoidance (r = .40), suggesting that these strategies are particularly salient for individuals with PTSD symptoms (Seligowski et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the significant relations between the aforementioned emotion regulation strategies and psychopathology, they have all demonstrated strong relations with symptoms of posttraumatic stress disorder (PTSD) as well (Seligowski et al, 2015). A recent meta-analysis of emotion regulation and PTSD reported that the largest average effect sizes (for specific strategies, rather than a general inability to regulate emotion) were Personality and Individual Differences 92 (2016) 104-108 for rumination (r = .51), thought suppression (r = .47), and experiential avoidance (r = .40), suggesting that these strategies are particularly salient for individuals with PTSD symptoms (Seligowski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation